Chipless RFID tag using RF MEMS switch. Issue 23 (1st November 2014) - Attaran, A.; Rashidzadeh, R.; Muscedere, R.
Abstract : A new chipless radio‐frequency identification (RFID) tag using the micro‐electro‐mechanical system (MEMS) technology is presented. The tag can operate at the conventional UHF band for RFID applications and can be implemented using a basic fabrication process. In the presented scheme, MEMS switches are used as programmable elements to support the communication between the tag and RFID interrogators.